A FUSED PET/MRI IN A PLANNING AND PERFORMING STEREOTACTIC OPERATIONS IN BRAIN TUMORS - A. I. Kholyavin; V. B. Nizkovolos; A. F. Gurchin; T. Yu. Skvortsova (Вестник рентгенологии и радиологии)
Objective – study of the diagnostic capabilities of MRI and PET/CT scanners and the available user programs for processing DICOM-images in the implementation of the preoperative planning of stereotactic interventions in patients with deep cerebral gliomas in terms of fusion the scans of a brain.Material and methods. 35 stereotactic surgeries (biopsies and treatment cryoablations) were preplanned and then conducted in patients with brain deep-seated tumors. Patients underwent MRI-scanning in stereotactic conditions and PET/CT scanning with the tumor-specific radiotracer 11C-methionine for stereotactic targeting in preoperative period. Stereotactic planning was conducted on fused MRI/PET images. A co-registration was carried out using a diagnostic workstation Philips and neuronavigation station Medtronic StealthStation S7.Results. A fusion of MRI and PET images using application software is a convenient tool for precise planning of target points and trajectories for insertion stereotactic cannula into a brain. On a fused image the PET-component enables to plan target areas for biopsy and selective ablation of the tumor, due to the ability of a radiotracer to accumulate selectively in the most malignant sites of a tumor. While MRI component, providing a clear anatomical visualization, allows the planning safe trajectories of stereotactic access out of eloquent areas, pathways of brain and intracerebral vessels, which reduces the risk of intraoperative complications. In addition, MRI provides imaging of fiducial markers for stereotactic calculations.Conclusion. High efficiency of preoperative planning on fused MRI/PET scans was demonstrated. The proposed planning method allows to increase the effectiveness of biopsies and to prevent the prolonged growth of brain glial tumors, even when their selective stereotactic ablation, as well as to ensure a low level of postoperative complications.